Leptin induces ADAMTS‐4, ADAMTS‐5, and ADAMTS‐9 genes expression by mitogen‐activated protein kinases and NF‐ĸB signaling pathways in human chondrocytes. (31st July 2014) - Yaykasli, Kursat Oguz; Hatipoglu, Omer Faruk; Yaykasli, Emine; Yildirim, Kubra; Kaya, Ertugrul; Ozsahin, Mustafa; Uslu, Mustafa; Gunduz, Esra
Abstract Elucidation of the causes of inflammation has vital importance in the development of new approaches for the treatment of arthritic diseases. The degradation of aggrecan by upregulated disintegrin and metalloproteinase with trombospondin motifs (ADAMTSs) is the key event in the development of both rheumatoid arthritis (RA) and osteoarthritis (OA). Increased levels of leptin in both RA and OA have been demonstrated, thus linking leptin to arthritic diseases, but the mechanism has not been clarified. This study investigated the putative role of signaling pathways (p38, JNK, MEK1, NF‐ĸB, and PI3) involved in leptin‐induced cartilage destruction. Normal human articular chondrocytes were cultured with recombinant human leptin at 100, 250, 500, and 1000 ng/mL doses for 6, 12, 24, and 48 h, after which ADAMTS‐4, ‐5, and ‐9 genes expression were determined by real time‐polymerase chain reaction (RT‐PCR) and Western Blot methods. The signaling pathways involved in leptin‐induced ADAMTSs upregulation were also investigated by using inhibitors of signaling pathways. It was demonstrated that ADAMTSs expression level was peaked at 1000 ng/mL doses for 48 hours, and MAPKs (p38, JNK, and MEK) and NF‐ĸB signaling pathways involving in leptin triggered ADAMTSs upregulation. Obesity as a risk for RA and OA may contribute to the inflammation of both RA and OA diseases by secreting adipokines like leptin. We hypothesize that leptin is involved in the development of RA and OA accompanied with obesity by increasing ADAMTS‐4, ‐5, and ‐9 genes expression via MAPKs and NF‐ĸB signaling pathways.